Sanksi Pidana Kebiri Kimia terhadap Pelaku Tindak Pidana Kekerasan Seksual Anak - I Komang Widnyana; Anak Agung Sagung Laksmi Dewi; Ni Made Sukaryati Karma (Jurnal Konstruksi Hukum, 2020)
The number of child sexual violence rates increased in 2016. Encourage the government to form Law of the Republic of Indonesia Number 17 of 2016 concerning Stipulation of PERPU Number 1 of 2016 concerning the Second Amendment to Law Number 23 of 2002 concerning Child Protection into Law. The law contains sanctions against perpetrators of child sexual violence in the form of chemical castration. The purpose of this study was to determine the regulation of chemical castration sanctions against perpetrators of child sexual violence. The method used is the normative method. The regulation for the imposition of criminal sanctions on chemical castration is regulated by Law No. 17 of 2016. The punishment system for chemical castration is a double track system of sanctions. Chemical castration sanctions are sanctions for the act of giving chemical substances to perpetrators of child sexual violence. The prosecutor will carry out the castration sanction as executor of the court's decision and may ask for help from non-doctor medical personnel. The government must immediately pass technical guidelines for the implementation of chemical castration measures. And there is a need for competency education to implement chemical castration.